APPROPRIATE INDUCTION OF T REGULATORY CELLS AND HBV TOLERANCE: IMPLICATIONS FOR IMMUNOTHERAPY OF AUTOIMMUNE DISEASES - Eltahir Khalid, Khalid; M. Ahmed, Mohammed El Imam; M Musa, Ahmed; Zang, Jingwu (مجلة الجزيرة للعلوم الصحية; مجلد 7 عدد 1 (2011), 2011)
Opposed to autoimmune diseases the immune tolerance to hepatitis B virus (HBV) has been related to inadequate HBV-specific immune response in addition to the high frequency and over expression of CD4+CD25+ T regulatory cells (Treg); however the exact mechanisms behind the induction of Treg cells in HBV infection are yet to be addressed. Generally Treg cells consist of diverse lymphocyte populations that include CD4+ cells, CD8+ cells, and other minor T cell populations. Several different mechanisms have been evolved to inhibit different immune responses, while many studies imply a cytokine-independent suppressive role of Treg cells in vitro , however accumulating evidence suggest the in vivo immunosuppressive activity of these cells against infection as well as autoimmunity needs cytokines. It is well documented that HBV Dane particles play a vital role in the immunopathogenesis of HBV infection and it has been associated with increased Treg cells which express various memory or activation markers. Based on that, alternative or indirect way of inducing Treg cells which could be a useful tool to ameliorate and/or treat autoimmune diseases is the top research priority. In this review we attempt to emphasize the role of HBV Dane particles (virions) on the induction of Treg cells and immune tolerance in HBV and we also discuss the relevance to search for new immunotherapeutic targets for autoimmune diseases.